Quark deconfinement in high-mass neutron stars - Orsaria, Milva Gabriela (2014)
In this paper, we explore whether or not quark deconfinement may occur in high-mass neutron stars such as J1614 - 2230 (1.97±0.04M) and J0348 + 0432 (2.01±0.04M). Our study is based on a nonlocal extension of the SU(3) Nambu-Jona-Lasinio (n3NJL) model with repulsive vector interactions among the quarks. This model goes beyond the frequently used local version of the Nambu-Jona-Lasinio (NJL) model by accounting for several key features of QCD which are not part of the local model. Confined hadronic matter is treated in the framework of nonlinear relativistic mean field theory. We find that both the local as well as the nonlocal NJL model predict the existence of extended regions of mixed quark-hadron (quark-hybrid) matter in high-mass neutron stars with masses of 2.1 to 2.4M. Pure quark matter in the cores of neutron stars is obtained for certain parametrizations of the hadronic lagrangian and choices of the vector repulsion among quarks. The radii of high-mass neutron stars with quark-hybrid matter and/or pure quark matter cores in their centers are found to lie in the canonical range of 12 to 13 km.